1997
DOI: 10.1074/jbc.272.8.4651
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Calcium-binding Protein That Interacts with the Integrin αIIb Cytoplasmic Domain

Abstract: The mechanism by which platelets regulate the function of integrin ␣ IIb ␤ 3 (or GPIIb/IIIa), the platelet fibrinogen receptor, is unknown but may involve the binding of proteins or other factors to integrin cytoplasmic domains. To identify candidate cytoplasmic domain binding proteins, we screened a human fetal liver cDNA library in the yeast two-hybrid system, using the ␣ IIb cytoplasmic domain as "bait," and isolated a novel 855-base pair clone. The open reading frame encodes a novel 191-amino acid polypept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
271
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 254 publications
(277 citation statements)
references
References 27 publications
4
271
0
1
Order By: Relevance
“…CIB1 is a Ca 2ϩ -binding protein (11). We therefore investigated whether KCl-induced Ca 2ϩ influx might modulate the action of CIB1 on ASK1 signaling in SH-SY5Y cells exposed to 6-OHDA.…”
Section: Cib1 Inhibits Traf2-ask1 Interaction and Ask1 Phosphorylatiomentioning
confidence: 99%
See 1 more Smart Citation
“…CIB1 is a Ca 2ϩ -binding protein (11). We therefore investigated whether KCl-induced Ca 2ϩ influx might modulate the action of CIB1 on ASK1 signaling in SH-SY5Y cells exposed to 6-OHDA.…”
Section: Cib1 Inhibits Traf2-ask1 Interaction and Ask1 Phosphorylatiomentioning
confidence: 99%
“…Calcium and integrin binding protein 1 (CIB1, also known as calmyrin) is a 22-kDa protein that shares substantial sequence similarity with calmodulin and several other calcium-binding proteins (11). CIB1 contains two canonical Ca 2ϩ -binding EFhand motifs in the COOH-terminal globular domain (12,13).…”
mentioning
confidence: 99%
“…5c). It should be noted that ␣ IIb -binding proteins have been identified (31,32); these proteins may be responsible for responding to or inducing this conformational switch (3). However, the conformational switch may be entirely intrinsic to the cytoplasmic tails of ␣ IIb and ␤ 3 , and positive or negative regulators may not be required to maintain the active and inactive states of the receptor.…”
Section: Resultsmentioning
confidence: 99%
“…Fnk interacts with the Ca 2+ /integrin-binding protein Cib Using the yeast two-hybrid-method and pull down assays we determined an interaction of Fnk and Cib (Kauselmann et al, 1999), a gene previously identi®ed as Ca 2+ /integrin binding protein (Naik et al, 1997). Deletion studies indicated that this interaction depends on the polo-box of Fnk.…”
Section: Fnk Overexpression Disrupts the F-actin Cytoskeleton Componentmentioning
confidence: 99%